(-3a)(2a)(-4a)=

Simple and best practice solution for (-3a)(2a)(-4a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3a)(2a)(-4a)= equation:


Simplifying
(-3a)(2a)(-4a) = 0

Remove parenthesis around (-3a)
-3a(2a)(-4a) = 0

Remove parenthesis around (2a)
-3a * 2a(-4a) = 0

Remove parenthesis around (-4a)
-3a * 2a * -4a = 0

Reorder the terms for easier multiplication:
-3 * 2 * -4a * a * a = 0

Multiply -3 * 2
-6 * -4a * a * a = 0

Multiply -6 * -4
24a * a * a = 0

Multiply a * a
24a2 * a = 0

Multiply a2 * a
24a3 = 0

Solving
24a3 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '24'.
a3 = 0

Simplifying
a3 = 0

The solution to this equation could not be determined.

See similar equations:

| x+8=x^2+4x-7 | | 8v+2(v+2)=-36 | | -5+13=5b-8-4b | | c=.5mv | | c=1/2mv | | -4=6x+2(-4x) | | 2.5x+6y=480 | | 5n^2-2n+28=0 | | -b=4a+3c-p | | X^5-3x+2x=0 | | 2xy-5=9 | | y=5+-10x | | -10x=-12 | | 13x+29y=-23 | | 20m-7-2m=8m-2 | | 2.3m+1=1.3m+7 | | -2-2=4-2X+3X | | 1/2*x-5=10 | | Y=-3/8x-2 | | 7.34=2(3.14)r | | e^8x+3=19 | | 15*500= | | 43x+2=38 | | 4w+2-3w=7 | | -4(x-4)=-3(x-7)-4 | | 5+10-5*2+45+2x=400 | | 40X+(1.5X)(5)=661 | | 8p-19=-28+7p | | 15+4a^2=2a^3-5 | | 4r-13=-15+5r | | -6(8-5r)=-r-6(1-4r) | | 5*2+10-5x=205 |

Equations solver categories